The role of strategic sustainability orientation, sustainable development practices and firm visibility on firm performance among micro, small and medium enterprises (MSMEs) in Malaysia - Mah, Pei Yew (2024)
Micro, small and medium enterprises (MSMEs) significantly impact Malaysia's economy, and their performance serves as the main catalyst for the country's economic growth. However, MSMEs encounter challenges in implementing sustainable development practices that could negatively impact their performance. This study investigates the effects of strategic orientation, corporate sustainability orientation, and sustainable development practices on the firm performance of MSMEs. The mediating effect of sustainable development practices in this relationship and the moderating effect of firm visibility between sustainable development practices and firm performance are also investigated. The data of 219 MSMEs from the service sector in Malaysia were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The result shows that strategic orientation and sustainable development practices impact the firm performance of MSMEs. Strategic orientation and corporate sustainability orientation contribute positively to enhancing sustainable development practices. MSMEs that integrate strategic orientation and corporate sustainability orientation actively engage in sustainable development practices, result in positive firm performance. However, corporate sustainability orientation did not influence firm performance, and firm visibility did not moderate the relationship between sustainable development practices and firm performance. Middle-level managers and service owners in MSMEs should integrate sustainability into their business goals, delegate implementation, and take action. In addition, policymakers should introduce appropriate programs and training to encourage greater adoption of sustainability practices in MSMEs. In terms of theoretical implications, this study extends the body of knowledge by integrating resource-based view theory, natural resource-based view theory and stakeholder theory into a single framework, and examines the linkages between strategic orientation, elements of sustainable development practices and firm performance.